The importance of SMA screening tests in newborns – review - Rusinowska, Barbara (Journal of Education, Health and Sport, 2022)
Spinal Muscular Atrophy (SMA) is an autosomal recessive neuromuscular disease caused by the loss of alfa motor neurons occuring with a frequency of 1 of 11000 births. It leads to muscular weakness and is cause of high rate of mortality in children. 95% cases of SMA are caused by homozygous deletion in SMN1 which is identified as the SMA disease-determining gene. The number of copies of SMN2 determines the phenotype of the disease. Screening tests for SMA can detect 95-98% of the mutations in SMN1, but cannot detect point mutations. The SMA genetic tests are characterized by high sensitivity and specificity, they are inexpensive and therefore can be used on a large scale. Generally DNA is isolated from the dry blood spot and then subjected to PCR analysis. The SMN2 copy number is determined using the MLPA technique. Screening tests allow the diagnosis of SMA even before the onset of symptoms. Numerous scientific studies show that early treatment in most patients with detected SMA allows for better neuromotor development in children. The most beneficial effects of the SMA therapy are visible in patients treated pre-symptomatically - and this is only possible thanks to the use of screening tests. In this review we present the importance of SMA screening tests in newborns according to the latest scientific reports.